Using Sniffer4D and SnifferV portable gas detectors for UAS monitoring of degassing at the Turrialba Volcano Costa Rica - Godfrey, Ian (2023)
Since the completion of the first Sniffer UAS payload research article titled; Using UAS with Sniffer4D Payload to Document Volcanic Gas Emissions for Volcanic Surveillance: In this study the UAS system deployed carried the Sniffer4D which tested for Temperature, Humidity and 9 additional parameters - Sulfur Dioxide SO2 (µg/ m3), Volatile Organic Compounds VOCs (ppm), Carbon Monoxide CO (mg/m3), Carbon Dioxide CO2 (µg/ m3), Ozone O3(µg/ m3), Nitrogen Dioxide NO2 (µg/ m3), O3+NO2 and Particulate Matter - PM 1.0, 2.5 & 10. We have since expanded our gas detection abilities by specifically configuring the Sniffer V (Volcanic), which has Sulfur Dioxide SO2 (µg/ m3), Carbon Monoxide CO (mg/m3), Flammable Gas CxHy (%), Hydrogen Sulfide H2S (µg/ m3), Carbon Dioxide CO2 (µg/ m3), Hydrogen chloride HCI (µg/ m3), Hydrogen H2 (%) and Hydrogen fluoride HF (µg/ m3). A consistent volcanic monitoring program is crucial to the safety of the population and the efficiency of the nation. Costa Rica´s National Commission for Risk Prevention the CNE helps manage this responsibility. The National Observatory for Volcanoes OVSCORI-UNA and the Atmospheric Chemistry Laboratory LAQAT-UNA of Universidad Nacional Costa Rica through a joint cooperation both have a strategic interest in monitoring and tracking volcanic activity. AN essential aspect of monitoring volcanoes is tracking the active emissions being released from the craters, subaerial and subaqueous fumaroles, and diffuse degassing through soil and cracks in the volcanic ediface. For this study the Sniffer4D gas detection payload was deployed on an UAS and flown directly into the active West Crater of the Turrialba volcano in September 2022 for readings of active emissions. The main objective was to characterize the volcanic plume of Turrialba for all of these parameters to establish a baseline that can be built upon in the future through additional measurements to determine changes in outgassing regime of the volcano. This was the second time the Turrialba volcano has been tested with Sniffer4D electrochemical gas detectors for these parameters.